Associations of Polymorphisms in HPC2/ELAC2 and SRD5A2 Genes with Benign Prostate Hyperplasia in Turkish Men - Izmirli, Muzeyyen; ARIKAN, BURHAN; BAYAZIT, YILDIRIM; ALPTEKİN, DAVUT (My University, 2011)
Benign prostate hyperplasia (BPH) is the most common benign tumor in elderly men for which the HPC2/ELAC2 and SRD5A2 genes are known genetic factors. The HPC2/ELAC2 gene features Ser217Leu and Ala541Thr polymorphisms and the SRD5A2 gene Ala49Thr and Val89Leu polymorphisms. The aim of this study was to examine relationships between these polymorphisms and BPH in Turkish men using amplification by the polymerase chain reaction (PCR) method. Polymorphisms were determined by using restriction fragment length polymorphism (RFLP) with suitable restriction: TaqI alpha, Fnu4HI, Mwo I and Rsa I. We found statistically significant relationship between the SRD5A2 gene Ala49Thr (OR=2.3; CI 95%, 1.04-5.1; p=0.01<0.05), but not the other polymorphisms, and BPH. For the first time, our data demonstrate that correlation between SRD5A2 gene Ala49Thr and polymorphism are statistically significant in Turkish men with BPH.